THE ROLE OF LEADER’S SPIRITUAL LEADERSHIP ON ORGANISATION OUTCOMES - Phuong V. Nguyen,; Khoa T. Tran,; Khanh Hai Dao,; Ho Phi Dinh, (Asian Academy of Management Journal, 2018)
This paper aims to investigate a causal model of spiritual leadership theory in organisational context and evaluates the effectiveness of spiritual survival and empowerment on organisational outcomes in terms of commitment and citizenship behaviour. It used structural equation model (SEM) approach to test a conceptual framework with data collection of 329 full-time employees working in service industries in Ho Chi Minh City, Vietnam. The findings illustrated the critical effects of spiritual leadership on organisational outcomes throughout membership, empowerment, and personal characteristics regarding meaning and calling. Specifically, a qualitative approach was conducted to highlight the testing results and get a better understanding of unanticipated consequences from the quantitative analysis. Based on the findings, the study proposed some specific interests of managerial implications and identify some limitations for future study.